Microstructural and microhardness characteristics of gas tungsten arc synthesized Fe-Cr-C coating on AISI 4340 - Buytoz, S; Yildirim, MM; Eren, H (Elsevier, 2005)
The effects of gas tungsten arc-processing (GTA) parameters on the microstructure and microhardness of Fe-Cr-C alloy coatings were investigated experimentally. Coatings were developed by GTA processing on an AISI 4340 steel substrate. Depending on the processing parameters, either hypoeutectic or hypereutectic microstructures were produced. The hypoeutectic microstructures consisted of primary dendrites of austenite (gamma) phase and eutectic M7C3 carbides. The hypereutectic microstructures consisted Of M7C3 primary carbides and eutectic. The formation of hypoeutectic or hypereutectic microstructures was influenced by the concentration of alloying elements (C, Cr). The hypereutectic microstructures showed higher hardness, which depend on the amount of powder delivered into the melt pool and extent of substrate melting. The lower hardness of hypoeutectic microstructure was related to the presence of austenite (gamma) phase in the primary dendrites and relatively low concentrations of Cr and C. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: M7C3 carbides; hardfacing; retained austenite; dendrite